2013
DOI: 10.1177/1049909113505138
|View full text |Cite
|
Sign up to set email alerts
|

End-of-Life Care Beliefs Among Hindu Physicians in the United States

Abstract: Several studies from the United States and Europe showed that physicians' religiosity is associated with their approach to end-of-life care beliefs. No such studies have focused exclusively on Hindu physicians practicing in the United States. A 34-item questionnaire was sent to 293 Hindu physicians in the United States. Most participants believed that their religious beliefs do not influence their practice of medicine and do not interfere with withdrawal of life support. The US practice of discussing end-of-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In a study of Hindu physicians working in the United States (Ramalingam et al, 2015), 80% of respondents acknowledged talking first with patients about DNR decision making and 70% involved family members in these DNR discussions. A total of 60% considered DNR to be allowed in Hinduism, and 86% did not believe that withdrawing life-support measures was in-congruent with their religious beliefs.…”
Section: Advance Directives and Treatment Discontinuation (See Table 1)mentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of Hindu physicians working in the United States (Ramalingam et al, 2015), 80% of respondents acknowledged talking first with patients about DNR decision making and 70% involved family members in these DNR discussions. A total of 60% considered DNR to be allowed in Hinduism, and 86% did not believe that withdrawing life-support measures was in-congruent with their religious beliefs.…”
Section: Advance Directives and Treatment Discontinuation (See Table 1)mentioning
confidence: 99%
“…A different American study showed that 86% of Hindu physicians do not think that their religious beliefs interfere with administration of terminal sedation, but only 6% of these healthcare providers reported having high intrinsic religiosity (Ramalingam et al, 2015). …”
Section: Artificial Nutrition and Hydration (Anh) And Pain Managementmentioning
confidence: 99%
“…A recent study investigated Hindu doctors' practices about talking to patients and families about do-not-resuscitate (DNR) orders, but the researchers did not identify the ethnicity of the patients they had cared for. 12 This study found that majority of the respondents talked to the patient before involving the family in DNR discussions and reported that their religious beliefs did not influence their medical practices such as withdrawing life support, sedation, giving intravenous fluids, and administering analgesia to patients with terminal illnesses. 12…”
Section: Introductionmentioning
confidence: 81%
“…12 This study found that majority of the respondents talked to the patient before involving the family in DNR discussions and reported that their religious beliefs did not influence their medical practices such as withdrawing life support, sedation, giving intravenous fluids, and administering analgesia to patients with terminal illnesses. 12…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation